2007
DOI: 10.1111/j.1570-7458.2007.00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Kairomonal response of the parasitoid Anagyrus spec. nov. near pseudococci to the sex pheromone of the vine mealybug

Abstract: The occurrence of a kairomonal response of the parasitoid Anagyrus spec. nov. near pseudococci (Hymenoptera: Encyrtidae) to (+)‐(1R,3R)‐cis‐2,2‐dimethyl‐3‐isopropenyl‐cyclobutanemethanol acetate (PcA, namely, planococcyl acetate) and (S)‐(+)‐lavandulyl senecioate (LS), the respective female sex pheromones of its hosts, the citrus mealybug, Planococcus citri (Risso) and the vine mealybug, Planococcus ficus (Signoret) (Homoptera: Pseudococcidae) was investigated. Attraction to the pheromones was tested by employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…Nitrogen is not included in coccoid pheromones but is necessary to operate their biosynthetic cascades. Moreover, pheromones are often perceived not only by conspecific mates, but also by natural enemies as kairomones: some coccoid pheromones are known to recruit predators and parasitoids [18,68,69]. These potential negative effects would have driven the loss of pheromone production in the asexual D. brevipes after the acquisition of parthenogenetic reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen is not included in coccoid pheromones but is necessary to operate their biosynthetic cascades. Moreover, pheromones are often perceived not only by conspecific mates, but also by natural enemies as kairomones: some coccoid pheromones are known to recruit predators and parasitoids [18,68,69]. These potential negative effects would have driven the loss of pheromone production in the asexual D. brevipes after the acquisition of parthenogenetic reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…ficus. Franco et al (2008c) showed, in light of both field and olfactometer experiments, that the females of the encyrtid Anagyrus spec. nov. near pseudococci, a major parasitoid of both the vine mealybug, Pl.…”
Section: Kairomonal Responsementioning
confidence: 98%
“…More recently, the VM sex pheromone (S)-(+)-lavandulyl senecioate (LS) proved to attract the females of the VM parasitoid A. sp. near pseudococci sensu Triapitsyn et al (2007) in field and under laboratory conditions (Franco et al, 2008b). This kairomonal response is an innate behavior trait (Franco et al, 2008b) and LS was shown to increase parasitism rates of mealybugs by A. sp.…”
Section: Introductionmentioning
confidence: 99%
“…near pseudococci sensu Triapitsyn et al (2007) in field and under laboratory conditions (Franco et al, 2008b). This kairomonal response is an innate behavior trait (Franco et al, 2008b) and LS was shown to increase parasitism rates of mealybugs by A. sp. near pseudococci in Mediterranean citrus orchards (Franco et al, 2008a, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation